Heat stress-induced nuclear transport mediated by Hikeshi confers nuclear function of Hsp70s. (June 2018) - Imamoto, Naoko
Abstract : The prime feature of eukaryotic cells is the separation of the intracellular space into two compartments, the nucleus and the cytoplasm. Active nuclear transport is crucial for the maintenance of this separation. In this report, we focus on a nuclear transport receptor named Hikeshi, which mediates the heat stress-induced nuclear import of 70-kDa heat shock proteins (Hsp70s), and discuss how the same protein can function differently depending on the cellular compartment in which it is localized. Hsp70 is a molecular chaperone that is predominantly localized in the cytoplasm under normal conditions but is known to accumulate in the nucleus under conditions of heat stress. Although the reported function of Hsp70 is mostly attributed to its molecular function in the cytoplasm, the functions of Hsp70 may extend beyond molecular chaperone activity in the nucleus.